2021
DOI: 10.21203/rs.3.rs-380804/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Acute ischemic stroke with cervical internal carotid artery steno-occlusive lesion: multicenter analysis of endovascular approaches

Abstract: Background Occlusions of internal carotid artery (ICA), whether isolated or in tandem lesions (TL) have a poor response to treatment with intravenous thrombolysis. Previous studies ​​have demonstrated the superiority of mechanical thrombectomy in the treatment of acute ischemic stroke (AIS) following large vessel occlusion, compared to standard intravenous fibrinolysis. The aim of our study was to describe endovascular treatment (EVT) in AIS due to ICA occlusion, whether isolated or in TL. Methods we assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Regrettably, we could not obtain any specific information regarding reasons for non-referral/non-acceptance for EMR. Likely contributing factors include: (1) "symptomatic" carotid disease being historically considered a primarily surgical disease, to be addressed within 14 days from symptom onset [23]; (2) CSCs primary focus on intracranial LVO management [8,19,20]; (3) unfamiliarity with the treatment of carotid origin disease under flow reversal [7,21,45]; (4) shortage of stroke MT centers [50,51]; and (5) lack of established pathways for emergency AIS-CA stroke referrals that would involve centers with expertise in endovascular carotid revascularization [49]. Furthermore, clinical practice suggests that rejection of a particular patient type will impact further referrals of similar patients.…”
Section: Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regrettably, we could not obtain any specific information regarding reasons for non-referral/non-acceptance for EMR. Likely contributing factors include: (1) "symptomatic" carotid disease being historically considered a primarily surgical disease, to be addressed within 14 days from symptom onset [23]; (2) CSCs primary focus on intracranial LVO management [8,19,20]; (3) unfamiliarity with the treatment of carotid origin disease under flow reversal [7,21,45]; (4) shortage of stroke MT centers [50,51]; and (5) lack of established pathways for emergency AIS-CA stroke referrals that would involve centers with expertise in endovascular carotid revascularization [49]. Furthermore, clinical practice suggests that rejection of a particular patient type will impact further referrals of similar patients.…”
Section: Limitationsmentioning
confidence: 99%
“…Carotid atherosclerotic disease is an important [1][2][3][4] yet underestimated [5] cause of ischemic stroke. Strokes of carotid bifurcation origin constitute at least 20% of ischemic strokes [1,6]; some of those present with a co-existing occlusion of the intracranial vessel(s) (tandem lesions) [7,8]. Acute ischemic stroke of extracranial carotid artery origin (AIS-CA) has an unfavorable clinical prognosis due to the large volume of affected brain tissue and the typically large thrombus load, with recanalization rates below 10% using systemic intravenous thrombolysis (IVT) [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Cirillo et al found that endovascular ICA stenting used in management of tandem occlusions led to improved revascularization and had improved long-term morbidity and mortality when compared to non-stenting techniques. [1] is methodology of endovascular intervention, in addition to MT, has been widely accepted as more successful compared to thrombolysis alone. e thrombectomy in tandem lesions collaboration compiled several cases of tandem occlusions involving the anterior circulation to compare the speed and rates of reperfusion in headfirst versus neck-first endovascular approaches.…”
Section: Introductionmentioning
confidence: 99%